Heparin algorithm for anticoagulation during continuous renal replacement therapy - Ostermann, Marlies (BioMed Central, 2010)
Premature circuit clotting is a problem during continuous renal replacement therapy. We describe an algorithm for individualised anticoagulation with unfractionated heparin based on the patient's risk of bleeding and previous circuit life. The algorithm allows effective and safe nurse-led anticoagulation during continuous renal replacement therapy.